Preparation, Process Optimization and Cytotoxicity Evaluation of Lyophilized Etoposide Loaded Nanoparticles: Pharmaceutical Science-Pharmaceutics for effective drug dosage - Priyal Patel; Shailesh Koradia; Falgun Mehta; Ashok Mahajan; Jayvadan Patel (International Journal of Life Science and Pharma Research, 2022)
The purpose of this study was to develop freeze dried Polylactide-co-glycolide (PLGA) nanoparticles loaded with etoposide intended to be administered intravenously with improved therapeutic efficacy of the drug and thereby reduced dose related toxicity associated with it. The etoposide loaded nanoparticles were prepared using modified spontaneous emulsification solvent diffusion method (SESD).The in Vitro release study of etoposide loaded Polylactide-co-glycolide (PLGA)–Nanoparticles NP was carried by dialysis bag diffusion technique.The incorporation efficiency was found to be higher in modified SESD technique than emulsification solvent evaporation method. The release behavior of etoposide exhibited a biphasic pattern characterized by an initial burst release followed by a slow and continuous release. The nanoparticles were characterized by particle size, zeta potential, polydispersity index, DSC and FTIR. The long term stability was achieved by lyophilisation technique. The cell line study using XTT assay on LNCaP prostate tumor cell lines revealed that etoposide loaded nanoparticles showed greater cancer cell inhibition compared to plain nanoparticles and marketed conventional formulations.